The conception of the circle of concerned African women theologians: is it African or western? - Fiedler, R. N.; Hofmeyr, J. W. (Faculty of Theology, University of the Free State, 2011)
In this article, we argue that the Circle of Concerned African Women Theologians was largely conceived as African, and that it addresses the issues of African women. The Circle approaches the issue of women’s liberation from an African perspective, and is not based on a Western concept. Thus, we will show how Mercy Amba Oduyoye and her mother experienced liberation in the African context. Furthermore, by reflecting on the experiences of Mercy Amba Oduyoye and her mother in the context of the men who formed part of their world (their husbands, grandfathers and uncles), we will show how the reinterpretation of oppressive African cultures by men can bring about the liberation of African women. This is in keeping with the agenda of the Circle, namely to liberate women in the church and in society. The ecumenical bodies merely provided the structures within which the Circle was organized. The influence of Western feminist theologies enshrined in the ecumenical bodies with which Mercy Amba Oduyoye was associated, therefore had only a limited impact on the conception of the Circle.
Keywords: Oduyoye, Mercy Amba; Oduyoye, Modupe; Masculinity; African feminist theology; Circle of concerned African women theologians